AWARENESS AND USE OF INFORMATION RESOURCES TO PROMOTE ENVIRONMENTAL PROTECTION AND CONSERVATION AT KENYA NATIONAL LIBRARY SERVICE, NAIROBI - Wangeci, Kuruga; Njoroge, Rose (African Journal of Education and Practice, 2021)
Purpose: This study sought to assess Awareness and use of environmental information resources to promote environmental protection & conservation at Kenya National Library Service Methodology: The study adopted descriptive research design. Simple random sampling was used to select a sample size of 105 respondents from a total target population of 550 staff members. In addition the five heads of department were interviewed. Data was collected and later analyzed both quantitatively and qualitatively. Frequency count and percentages were used to analyze the data collected. Results: Findings revealed that the level of awareness on environmental information resources is low since the KNLS library staff has not implemented methods of awareness creation to users. The environmental information resources in Kenya National Library Service are not located at a specific place but integrated with the rest of the library collection thus hard to locate with ease. The challenges faced by Kenya National Library Services staff in disseminating environmental information resources to the users. Unique contribution to theory, practice and policy: Libraries and relevant environmental institutions need to create awareness on environmental information resources, conduct staff training, and evaluation of environmental information resources so as to access the level of quality and value to the library users.